2011
DOI: 10.1016/j.cell.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Elements Regulate Cytoplasmic mRNA Decay

Abstract: Promoters are DNA elements that enable transcription and its regulation by trans-acting factors. Here, we demonstrate that yeast promoters can also regulate mRNA decay after the mRNA leaves the nucleus. A conventional yeast promoter consists of a core element and an upstream activating sequence (UAS). We find that changing UASs of a reporter gene without altering the transcript sequence affects the transcript's decay kinetics. A short cis element, comprising two Rap1p-binding sites, and Rap1p itself, are neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
170
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 50 publications
3
170
1
Order By: Relevance
“…They may include 3′ end formation and coupled polyadenylation, splicing, mRNA export as well as cytoplasmic events involving translation, RNA binding proteins (RBP) and miRNAs (Joshi et al, 2012). Interestingly, a few recent reports highlight the tight coupling between transcriptional regulation and post-transcriptional events that govern mRNA stability (Bregman et al, 2011; Trcek et al, 2011). In these examples, RBPs are recruited by specific transcription factors, which then help load the RBPs onto nascent RNA; they then control cytoplasmic mRNA stability (Bregman et al, 2011; Trcek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may include 3′ end formation and coupled polyadenylation, splicing, mRNA export as well as cytoplasmic events involving translation, RNA binding proteins (RBP) and miRNAs (Joshi et al, 2012). Interestingly, a few recent reports highlight the tight coupling between transcriptional regulation and post-transcriptional events that govern mRNA stability (Bregman et al, 2011; Trcek et al, 2011). In these examples, RBPs are recruited by specific transcription factors, which then help load the RBPs onto nascent RNA; they then control cytoplasmic mRNA stability (Bregman et al, 2011; Trcek et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a few recent reports highlight the tight coupling between transcriptional regulation and post-transcriptional events that govern mRNA stability (Bregman et al, 2011; Trcek et al, 2011). In these examples, RBPs are recruited by specific transcription factors, which then help load the RBPs onto nascent RNA; they then control cytoplasmic mRNA stability (Bregman et al, 2011; Trcek et al, 2011). A mechanism of this nature could account for the post-transcriptional generation of rhythmic mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present demonstration that mammalian TFs can actively participate in the process of cytoplasmic mRNA degradation was highly unexpected, our work comes in the wake of recent genetic and molecular evidence establishing functional coupling between mRNA synthesis and degradation in yeast [42][43][44] . In particular, specific promoter sequences in yeast have been shown to influence cytoplasmic mRNA decay, presumably through their associated TFs 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in yeast and humans indicated that these processes are interconnected and that cis-acting sequences help to coordinate transcription and mRNA decay (Goler-Baron et al 2008;Bregman et al 2011). Moreover, these data implied that TFs regulate distinct processes of gene expression by interacting with multiple cofactors dedicated to individual steps in gene expression and/or with protein complexes that harbor multiple functional activities.…”
Section: Discussionmentioning
confidence: 99%